DIFFERENTIAL ALLELOPATHIC ACTIVITY OF PARTHENIUM HYSTEROPHORUS L. AGAINST CANARY GRASS AND WILD OAT - F. Aslam; A. Khaliq; A. Matloob; R. N. Abbas; S. Hussain; F. Rasul (Journal of Animal and Plant Sciences, 2014)
Allelopathic effects of invasive weed parthenium (Parthenium hysterophorus L.) were studied by using whole plant, leaf and root aqueous extracts at 0, 2.5, 5.0, 7.5 and 10% (w/v) concentrations against germination and early seedling growth of wild oat (Avena fatua L.) and canary grass (Phalaris minor Retz.). Studies were carried out in Petri plates using filter paper as substratum placed in controlled conditions and soil-filled plastic pots placed in open environments. Both the experiments were laid out in a completely randomized design using four replicates. Pronounced variation was noticed for allelopathic activity of different plant parts of parthenium, extract concentrations, test species, and bioassay techniques. Parthenium extracts either inhibited or delayed the germination and suppressed seedling growth of test species. Various germination and seedling growth attributes were diminished to a much greater extent in Petri plates than in soil. Soil application of these extracts failed to reproduce results identical to those achieved in Petri plates, suggesting variable allelopathic response under different bioassay techniques. Leaf extracts were more suppressive to germination of test species than whole plant and root extracts in both Petri plates and pot studies at all concentrations. Highest chlorophyll inhibition coupled with enhanced tissue phenolic contents was recorded by aqueous extracts of parthenium in both the test species. Canary grass appeared to be more susceptible than wild oat at all concentrations of aqueous extracts. It is concluded that bioassays conducted under controlled condition using filter paper as substratum may be misleading due to over estimation of allelopathic response and variation in potential of receiver and donor species. Hence, allelopathic bioassays must consider the components of natural settings in order to generate ecologically reliable information.
Keywords: Allelopathic inhibition; aqueous extracts; bioassays; germination dynamics; phenolics; seedling growth